Strategic dimensions of personal image : how much does it cost? - Chiew, Han Yong. (2008)
Impression management, the process by which people control the impression others form of them, plays an important role in interpersonal behavior. It has been argued that creating a good first impression during a job interview increases one’s chances of getting employed. This project examines what are important in a job interview, as well as the significance of impression management during an interview.